How to win friends and influence fungi : collected quirks of science, tech, engineering, and math from nerd nite - Balakrishnan, Chris; Wasowski, Matt.; Orr, Kristen (New York: St. Martin's Press, 2024)
"In the vein of acclaimed popular-science bestsellers such as Atlas Obscura, Astrophysics for Young People in a Hurry, The Way Things Work, What If?, and Undeniable, the co-founders of the global science organization Nerd Nite bring readers a collection of wacky, yet fascinating STEM topics. For 20 years, Nerd Nite has delivered to live audiences around the world, the most interesting, fun, and informative presentations about science, history, the arts, pop culture, you name it. There hasn't been a rabbit hole that their army of presenters hasn't been afraid to explore. Finally, after countless requests to bring Nerd Nite to more fans across the globe, co-founders and college pals Matt Wasowski and Chris Balakrishnan are bringing readers the quirky and accessible science content that they crave in book form, focused on STEM and paired with detailed illustrations that make the content pop. The resulting range of topics is quirky and vast, from kinky, spring-loaded spiders to the Webb telescope's influence on movie special effects. Hilariously named after Dale Carnegie's iconic book, How to Win Friends and Influence Fungi features narratives, bursts, and infographics on all things STEM from scientists around the world. Chapters are sure to make you laugh-out-loud, with titles such as "The Science of the Hangover," "What Birds Can Teach Us About the Impending Zombie Apocalypse," and "Lessons from the Oregon Trail." With fascinating details, facts, and illustrations, combined with Chris and Matt's incredible connections to organizations such as the Discovery Network and the Smithsonian Institution, How to Win Friends and Influence Fungi is sure to reach joyful STEM enthusiasts of all ages around the world. About Nerd Nite: Started in 2003, Nerd Nite is a monthly event held in 100+ cities worldwide during which folks give 20-minute fun-yet-informative presentations across all disciplines, while the audience drinks along!"
Keywords: Science. -- Miscellanea; Science. -- Humor; Medicine -- Miscellanea; Medicine -- Humor; Technology -- Miscellanea; Technology -- Humor